Parental and peer influences on the choice of career among first-year undergraduate students - Abd Karim, Aishah Hanim (Asian Scholars Network, 2024)
Career decision-making is very crucial among young adults. Some of them may face dilemmas in choosing their desired career path. Parental and peer views play important roles in every aspect of an individual’s life, including academic and personal matters. The present study aims to investigate the influence of parent and peer on first-year undergraduate students’ career choice. This research was conducted by looking at the issue whereby undergraduate students struggled to decide on their future career. The study applied a qualitative method and phenomenological research design involving five first-year undergraduate students from the Faculty of Education. The researcher utilized individual semi-structured interviews as the data collection method. Data gained were transcribed, coded, categorized, and analyzed using the thematic analysis. The findings revealed that parents and peers do influence the career choice of first-year undergraduate students. This research concludes that it is important for undergraduate students to have firm decision-making skills to help them in making good career choice.